Analisis Implementasi Komunikasi Efektif Pada Petugas Pendaftaran Terhadap Pasien Baru Rawat Jalan Di Rumah Sakit Setia Mitra - Yayah Sya'diah,SST,MKes.; Nadisa Sabrina Kevinita Sabrina Kevinita (APIKES Bhumi Husada Jakarta, 2023)
ABSTRACT Effective communication of officers is very important to give a good impression at the beginning of service at the hospital. Problems related to effective communication in registration services are that officers do not receive training and seminars. The study was conducted to determine the implementation of effective communication of outpatient registration officers at Setia Mitra Hospital. The research was conducted using qualitative and quantitative descriptive analysis methods with data collection techniques by observation, interviewing officers, and patient surveys. The research sample consisted of 10 registration officers and 94 new patients. The results of the study were the highest compliance rate of 100% when the officers asked for patient visits and identity interviews. The compliance rate is 40% when officers provide 3S and are quick to respond. The compliance rate is 30% when officers provide clear, friendly, and pleasant information, providing a comfortable and conducive situation. The lowest compliance rate was 20% when the officer thanked him in a friendly manner. Officers have consistently implemented SOPs, but there are several SOPs that have not been implemented.